2012
DOI: 10.1021/nn302310q
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Infused Nanostructured Surfaces with Extreme Anti-Ice and Anti-Frost Performance

Abstract: Ice-repellent coatings can have significant impact on global energy savings and improving safety in many infrastructures, transportation, and cooling systems. Recent efforts for developing ice-phobic surfaces have been mostly devoted to utilizing lotus-leaf-inspired superhydrophobic surfaces, yet these surfaces fail in high-humidity conditions due to water condensation and frost formation and even lead to increased ice adhesion due to a large surface area. We report a radically different type of ice-repellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
983
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,171 publications
(1,000 citation statements)
references
References 21 publications
12
983
2
3
Order By: Relevance
“…The addition of a lubricant to form a SLIPS coating drastically reduces the adhesion of ice by more than one order of magnitude compared to the superhydrophobic substrate (by decoupling the ice formation from the solid substrate). The measured ice adhesion strength on the transparent SLIPS coating (10 ± 7 kPa) is in excellent agreement with our previous results on SLIPS coatings on aluminium 21 , suggesting that the surface properties are governed by the lubricant layer and not the solid substrate itself.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The addition of a lubricant to form a SLIPS coating drastically reduces the adhesion of ice by more than one order of magnitude compared to the superhydrophobic substrate (by decoupling the ice formation from the solid substrate). The measured ice adhesion strength on the transparent SLIPS coating (10 ± 7 kPa) is in excellent agreement with our previous results on SLIPS coatings on aluminium 21 , suggesting that the surface properties are governed by the lubricant layer and not the solid substrate itself.…”
Section: Resultssupporting
confidence: 90%
“…The strong adhesion of ice to most common surfaces, causing safety and economic issues in any technology subjected to subzero environments, is another example where the direct contact of the material with the substrate is the principal cause for its detrimental effects. We recently demonstrated that SLIPS coatings based on highly textured polypyrrole drastically lower strength of ice adhesion to aluminium substrates 21 . Of further importance is the ability to impart transparency to such icerepellent coatings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations